Linguistic Features of Banyuwangi Traditional Culinary Terms and Osing Cultural Identity - Aminulloh, Aminulloh; Rastitiati, Ni Kade Juli; Pradana, Wayan Radita Yuda; Yanyan, Bi; Subayil, Subayil (Journal of Language Intelligence and Culture, 2025)
Culinary language helps express and preserve cultural identity; however, the linguistic features of Banyuwangi traditional culinary terms and their links to Osing culture remain underexplored. This study analyzes the phonological, morphological, semantic, and pragmatic characteristics of these terms and examines how they function as markers of Osing identity. Using a qualitative descriptive design, the research combines semi-structured interviews, participant observation in traditional food settings, and document analysis of local recipe books and menus. The findings demonstrate that these terms constitute a robust yet flexible lexicon with basic sound symbolism, wide use of compounding, many descriptive meanings and lots of metaphorical creativity that enhance memorability, oral transmission and change. While showing these words being pragmatically deployed as semiotic resources in actions localizing identity and voicing community pride, also participates in cultural branding of Banyuwangi as different by combining them with Indonesian or English classifiers to create hybrid tourism labels. Linking a detailed formal analysis of terms for foods with identity-oriented socialist, this study cries out for linguistics and provides a valuable lexical resource for classroom teaching about cultural difference in local-content and intercultural curricula as well as its contribution to local culture heritage and tourism program.